2022
DOI: 10.1155/2022/7851436
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Application Value of High-Frequency Ultrasound Combined with Detection of Serum High Mobility Group Box 1, Soluble IL-2 Receptor, and Thyroglobulin Antibody in Diagnosing Thyroid Cancer

Abstract: Objective. The aim of this study is to explore the clinical application value of high-frequency ultrasound combined with detection of serum high mobility group box (HMGB-1), soluble IL-2 receptor (SIL-2R), and thyroglobulin antibody (TgAb) in diagnosing thyroid cancer. Methods. By means of retrospective study, 50 thyroid cancer patients treated in our hospital from January 2019 to January 2021 were selected as the thyroid cancer group, 50 patients with benign thyroid lesions were included in the benign lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thyroxine suppressive treatment in patients may increase the serum level of sIL-2R because thyroid hormones can inversely modulate the cell-mediated immune response [19]. High-frequency ultrasound combined with the detection of serum high mobility group box (HMGB-1), sIL-2R, and thyroglobulin antibody level (TgAb) has diagnostic power in thyroid cancer (sensitivity: 98.0% and specificity: 95.0%) [25]. However, there was limited research currently available on the relationship between serum sIL-2R and PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroxine suppressive treatment in patients may increase the serum level of sIL-2R because thyroid hormones can inversely modulate the cell-mediated immune response [19]. High-frequency ultrasound combined with the detection of serum high mobility group box (HMGB-1), sIL-2R, and thyroglobulin antibody level (TgAb) has diagnostic power in thyroid cancer (sensitivity: 98.0% and specificity: 95.0%) [25]. However, there was limited research currently available on the relationship between serum sIL-2R and PTC.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%